Pengaruh Kombinasi Metode Bobath dan Neurosensomotor untuk Peningkatan Postural Kontrol Duduk pada Delay - M.Or, TITIN KARTIYANI (Universitas Pekalongan, 2021)
ABSTRACT In this case of growth and development, the prevalence of significant growth retardation in the pediatric population is not yet clear. Through statistical calculations, 2-3% of infants are outside the range of normal motor milestones. Of this number, a small proportion (15-20%) are known to have a diagnosis of significant growth and development disorders in the form of cerebral palsy or defects at birth. A child's growth and development disorder, commonly known as Delay Development, is a disorder that attacks the child's growth and development process, in this case, a child's growth and development disorders such as cognitive, gross motoric, fine and emotional. The purpose of this study was to determine whether there is an effect of a combination of bobath exercise and neurosensomotor on sitting postural control on developmental delay. This research is a pre-experimental design, with a one group pretest-post test design. After the difference test between pre-test data and post-test data using Paired T-test, the results were p = (p